The Effect of Communication, Competency and Motivation on Employee Performance: The Case of Population and Civil Registration Office of Palembang City - Saputra, Yandhi Eka; Djazuli, Abid; Choiriyah, Choiriyah (International Journal of Business, Management and Economics, 2025)
This study aims to determine 1) the Effect of Communication, Competence, and Work Motivation on Employee Performance at the Population and Civil Registration Service of Palembang City. 2) The Effect of Communication on Employee Performance at the Population and Civil Registration Service of Palembang City. 3) The Influence of Competence on the Performance of Employees of the Population and Civil Registration Service of Palembang City. 4) The Influence of Work Motivation on the Performance of Employees of the Population and Civil Registration Service of Palembang City. This type of research is Associative. The variables used by researchers include Communication, Competence, Motivation, and Performance. The population of this study consisted of all Employees of the Population and Civil Registration Service of Palembang City, and the sample size in the study amounted to 101 employees. The sampling technique used was Proportionate Stratified Random Sampling. The data used in this study are primary data collected through a questionnaire. The data analysis technique used is multiple linear regression. The results of this study indicate that: 1) Communication, Competence, and Motivation have a significant effect on the Performance of Employees of the Population and Civil Registration Service of Palembang City. 2) Communication has a significant effect on the Performance of Employees of the Population and Civil Registration Service of Palembang City. 3) Competence significantly influences the performance of employees at the Palembang City Population and Civil Registration Service. 4) Motivation significantly influences the performance of employees at the Palembang City Population and Civil Registration Service.